The Economics of Variable Renewables and Electricity Storage - Javier López Prol; Wolf-Peter Schill (ZBW - Leibniz Information Centre for Economics, 2021)
The transformation of the electricity sector is a main element of the transition to a decarbonized economy. Conventional generators powered by fossil fuels have to be replaced by variable renewable energy (VRE) sources in combination with electricity storage and other options for providing temporal flexibility. We discuss the market dynamics of increasing VRE penetration and their integration in the electricity system. We describe the merit-order effect (decline of wholesale electricity prices as VRE penetration increases) and the cannibalization effect (decline of VRE value as their penetration increases). We further review the role of electricity storage and other flexibility options for integrating variable renewables, and how storage can contribute to mitigating the two mentioned effects. We also use a stylized open-source model to provide some graphical intuition on this. While relatively high shares of VRE are achievable with moderate amounts of electricity storage, the role of long-term storage increases as the VRE share approaches 100%.
Keywords: Q42; 330; energy transition; decarbonization; variable renewable energysources; electricity storage; merit-order effect; cannibalization effect